Flood Routing of Tigris River in Baiji Station and Makhoul Dam Reservoir under Supposed Operation of the Dam - Ghassan Shalan Nida Al-Shahry; Sabbar Abdullah Saleh (Tikrit Journal of Pure Science, 2023)
The digital elevation models (DEM) used for geometric analysis of the reservoir, as essential requirement  in the study of flood routing in the reservoir and in Baiji station on Tigris river, the volume of storage, volume of island, positive and negative planner area and surface areas, residual capacity, reservoir average depth, and average thickness of the island, were estimated, at each hypothetical level from 108-160 meters above sea level, the geometric elements of storage volume and residual capacity are used directly for flood routing.